Viscosity decoupled charge transport in surface functionalized ZnS nanoparticle dispersed imidazolium ionanofluids. (August 2019) - Deb, Debalina; Dutta, Bula; Bhattacharya, Subhratanu
Graphical abstract: Highlights: Imidazolium Ionic liquid based ZnS nanoparticles dispersed nanofluid were developed. The thermophysical properties of nanofluids were studied. Temperature-dependent electrical properties of the nanofluids were studied. Viscosity decupled charge transport was observed. Correlation between thermophysical and electrical properties were established. Abstract: The mechanism of charge transport in ionic liquid functionalized ZnS nanoparticles dispersed imidazolium-based ionanofluids are investigated combining impedance spectroscopy, viscosity measurement and diﬀ ;erential scanning calorimetry. The viscosity enhances from 76 mPa S to 229 mPa S at room temperature in 0–20 wt% of functionalised nanoparticles addition in the ionic liquid. The conductivity and permittivity spectra are dominated on the low-frequency side by electrode polarization effects. Using the Poisson–Nernst–Planck (PNP) electro-diffusion equations enables us to determine the dc conductivity, ion diffusivity and hopping length of mobile ions and their nature of thermal activation. A decoupling of ion transport with viscosity is observed in the ionanofluids within the entire temperature range and for the 15.0 wt% nanoparticle inserted nanofluid conductivity reaches a maximum value (2.5 mS/cm at 30 °C). The physical explanation regarding the possible origin of the observed remarkable decoupling is proposed.